The Influence of Organizational Culture, Work Environment and Workload on Employee Performance - Rahmat, Abdul; Christina, Christina (Dinasti Publisher, 2024)
This study aims to analyze the influence of organizational culture, work environment, and workload on employee performance. Population in this research is 35 employees of PT. Sunrider Nusaperdana. The sample used is 35 employees, with a saturation sampling, meaning the entire population is used as the sample. Data collection method uses field research, with the research instrument being a questionnaire measured using a Likert scale. Data analysis method uses component or variance-based structural equation modeling, processed using the Partial Least Square (Smart-PLS) version 3.0 program. The research design used is a causal research with a quantitative approach. This study proves that the organizational culture variable has an original sample value of 0.363, t-statistics of 4.146 > 1.96, and a p-value of 0.000 < 0.05, meaning that organizational culture has a positive and significant influence on employee performance. The work environment variable has an original sample value of 0.176, t-statistics of 3.584 > 1.96, and a p-value of 0.000 < 0.05, meaning that the work environment has a positive and significant influence on employee performance. The workload variable has an original sample value of 0.468, t-statistics of 6.002 > 1.96, and a p-value of 0.000 < 0.05, meaning that workload has a positive and significant influence on employee performance.